Osseointegration effects of local release of strontium ranelate from implant surfaces in rats - Alenezi, Ali (Clinical oral implants research, 2018)
Background:  Numerous studies have reported the beneficial effects of strontium on bone growth, particularly by stimulating osteoblast proliferation and differentiation. Thus, strontium release around implants has been suggested as one possible strategy to enhance implant osseointegration. Aim/Hypothesis:  This study aimed to evaluate whether the local release of strontium ranelate (Sr-ranelate) from implants coated with mesoporous titania could improve bone formation around implants in an animal model. Material and Methods:  Mesoporous titania (MT) thin coatings were formed utilizing the evaporation induced self-assembly (EISA) method using Pluronic (P123) with or without the addition of poly propylene glycol (PPG) to create materials with two different pore sizes. The MT was deposited on discs and mini-screws, both made of cp Ti grade IV. The MT was loaded with Sr-ranelate using soaking and the drug uptake and release kinetics to and from the surfaces were evaluated using quartz crystal microbalance with dissipation monitoring (QCM-D) utilizing a Q-sense E4 instrument. For the in vivo experiment, 24 adult rats were analyzed at two time points of implant healing (2 and 6 weeks). Titanium implants shaped as mini screws were coated with MT films and divided into two groups supplied with Sr-ranelate (test group) and without Sr-ranelate (control group). Four implants (both test and control) were inserted in the tibia of each rat. The in vivo study was evaluated using histomorphometric analyses. Results:  SEM images showed the successful formation of evenly distributed MT films covering the entire surface with pore sizes of 6 nm and 7.2 nm, respectively. The QCM-D analysis revealed an absorption of 3300 ng cm 2 of Sr-ranelate on the 7.2 nm MT, which was about 3 times more than the observed amount on the 6 nm MT (1200 ng cm 2 ). Both groups showed sustained release of Sr-ranelate from MT coated discs. The histomorphometric analysis revealed no significant differences in bone implant contact (BIC) and bone area (BA) between the implants with Sr-ranelate and implants in the control groups after 2 and 6 weeks of healing (BIC with a p -value of 0.43 after 2 weeks and 0.172 after 6 weeks BA with a p -value of 0.503 after 2 weeks, and 0.088 after 6 weeks). The mean BIC and BA values within the same group showed significant increase among all groups between 2 and 6 weeks. Conclusions and Clinical Implications:  This study could not confirm any positive effects of Sr-ranelate on implant osseointegration.